2021
DOI: 10.3390/ma14082020
|View full text |Cite
|
Sign up to set email alerts
|

Research on High- and Low-Temperature Characteristics of Bitumen Blended with Waste Eggshell Powder

Abstract: The sustainability of resources is presently a major global concern. Sustainable construction materials can be produced by applying biological waste to engineering. Eggshells, as biological waste, are usually dumped in landfills or discarded. This causes many environmental problems including malodor, noise pollution, and serious waste of resources. To solve these problems, this study combined eggshell waste with bitumen materials for bio-roads construction. This paper investigated the impact of biological wast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The stiffness modulus and stiffness dissipation rate (m-value) obtained from the BBR test are the main parameters for characterizing the low-temperature performance of bitumen. Furthermore, the direct tensile test at extremely low temperature is used to determine the critical cracking temperature of bitumen [ 14 , 15 , 16 ]. The advanced rheological tests, as mentioned above, have not been applied for the characterization and optimization of hydraulic bitumen binders.…”
Section: Introductionmentioning
confidence: 99%
“…The stiffness modulus and stiffness dissipation rate (m-value) obtained from the BBR test are the main parameters for characterizing the low-temperature performance of bitumen. Furthermore, the direct tensile test at extremely low temperature is used to determine the critical cracking temperature of bitumen [ 14 , 15 , 16 ]. The advanced rheological tests, as mentioned above, have not been applied for the characterization and optimization of hydraulic bitumen binders.…”
Section: Introductionmentioning
confidence: 99%
“…Francis et al [60] examined the impact of the addition of chicken eggshell powder on the compressed concrete and reported that addition of WCES led to improvement in the density, compressive strength, and durability of the concrete. The effect of the addition of various percentages of WCES to asphalt was investigated by Wang et al [61][62][63] who revealed improved strength, hardness, and thermal stability of the bitumen. Table 2 is a compilation of the outcomes of some researches on the application of WCES as cement additive and partial concrete replacement.…”
Section: Construction Applicationsmentioning
confidence: 99%
“…To evaluate the rheological properties of the asphalt mortars, the high and intermediate temperature sweep tests were conducted in strain-controlled loading mode at a constant frequency of 10 rad•s −1 using a Malvern Kinexus (UK) DSR test device [16,41,42]. For the high-temperature sweep tests, a parallel plate with 25 mm diameter and 1 mm gap was used.…”
Section: Rheological Property Testingmentioning
confidence: 99%